GAPS BETWEEN RESETTLEMENT POLICY OF SLEMAN REGENCY AND VICTIM'S PREFERENCES AFTER MOUNT MERAPI ERUPTION IN 2010 - RAHMAN, ABDUR ([Yogyakarta] : Universitas Gadjah Mada, 2012)
problems because of the victims who lost their homes. The victims had lived in five villages, i.e. Kepuharjo, Umbulharjo, Glagaharjo, Wukirsari, and Argomulyo, they should be relocated. This research aims to analyze resettlement preferences of the victims by Mt. Merapi eruption 2010, to analyze gaps between the policy of Sleman Regency regarding handling of victims and the victims' preferences, and to analyze satisfaction living in the villages of the victims after Mt. Merapi Eruption 2010. The analysis of field observation and questionnaire result to the victims and to key person of Sleman Regency reveal that there were gaps between Sleman Regency and the people, during evacuation process and resettlement program after 2010 eruption. 1) Some people especially at the Kinahrejo Hamlet, the Umbulharjo Village, did not want to evacuate during the eruption. It indicates that there was the lack of trust to government warning regarding Mt. Merapi activity. 2) There is a difference between the resettlement program of Sleman Regency and the victims' preferences. Sleman Regency planned to designate the area around Mt. Merapi crater and the Gendol River bank located along 10 km from the crater in the Dangerous Zone III as forbidden zones, but many victims did not want to move from their original villages. The questionnaire regarding resettlement preferences to 100 victims reveals that 1) the number of respondents who did not leave their villages was 90% and 70 %, respectively before and after eruption. 2) Factor Analyses reveal that safety from Mt. Merapi eruption, social relationship, personal attributes (age, length of stay, and education), amenity of environment, environmental satisfaction, and job activities affect on the victims' resettlement preferences. Questionnaire result shows that 55 respondents very satisfied the living on Mt. Merapi slope and 33 respondents satisfied. Multiple Regression Analyses reveal that satisfaction with living in their villages on Mt. Merapi is depended on "community" with good relationship among the residents, "amenity" living in the village, and "convenience" regarding facilities and accessibilities.